Case report: Immunovirotherapy as a novel add-on treatment in a patient with thoracic NUT carcinoma - Kloker, Linus D.; Calukovic, Branko; Benzler, Katrin; Golf, Alexander; Böhm, Sebastian; Günther, Sven; Horger, Marius; Haas, Simone; Berchtold, Susanne; Beil, Julia; Carter, Mary E.; Ganzenmueller, Tina; et al. (Frontiers in Oncology, 2022)
NUT carcinoma (NC) is a rare and extremely aggressive form of cancer, usually presenting with intrathoracic or neck manifestations in adolescents and young adults. With no established standard therapy regimen and a median overall survival of only 6.5 months, there is a huge need for innovative treatment options. As NC is genetically driven by a single aberrant fusion oncoprotein, it is generally characterized by a low tumor mutational burden, thus making it immunologically cold and insusceptible to conventional immunotherapy. Recently, we have demonstrated that oncolytic viruses (OVs) are able to specifically infect and lyse NC cells, thereby turning an immunologically cold tumor microenvironment into a hot one. Here, we report an intensive multimodal treatment approach employing for the first time an OV (talimogene laherparepvec (T-VEC); IMLYGIC®) together with the immune checkpoint inhibitor pembrolizumab as an add-on to a basic NC therapy (cytostatic chemotherapy, radiation therapy, epigenetic therapy) in a patient suffering from a large thoracic NC tumor which exhibits an aberrant, unique BRD3::NUTM1 fusion. This case demonstrates for the first time the feasibility of this innovative add-on immunovirotherapy regimen with a profound, repetitive and durable replication of T-VEC that is instrumental in achieving tumor stabilization and improvement in the patient ́s quality of life. Further, ́a previously unknown BRD3::NUTM1 fusion gene was discovered that lacks the extraterminal domain of BRD3.